RAFFINOSE, STACHYOSE AND SUCROSE CONTENTS OF MUNG BEAN CULTIVARS DIFFERING IN SEED COAT COLOR FROM HYDERABAD-KARNATAKA REGION OF INDIA: EFFECT OF SOAKING AND GERMINATION - MUHAMMED TAJODDIN; MANOHAR SHINDE; LALITHA JUNNA (The Bioscan, 2010)
Ten samples of mung bean (Vigna radiata L.) cultivars including three yellow cultivars representing a broad range of varietal characteristics from Hyderabad-Karnataka region of India were subjected to analysis for their oligosaccharide content. Further, the effect of soaking and germination on the levels of oligosaccharides (raffinose, stachyose and sucrose) contents were investigated. The level of sucrose, raffinose and stachyose in different cultivars of mung beans was found to be in the range from 0.84 to 1.71%, 0.62 to 1.05% and 1.75 to 3.57% respectively. The total level of sucrose, raffinose and stachyose was ranged between 3.48 to 5.37%. The processing methods like soaking and germination reduced oligosaccharide content considerably. Soaking for 12 hr led to the decrease in sucrose by 29 to 70%, raffinose by 19 to 74% and stachyose by 28 to 57% respectively. Compared with soaking, soaking followed germination appeared to be more efficient on the reduction of oligosaccharide content. Germination for 48 hr decreased raffinose and stachyose contents considerably, while sucrose increased by 25-52%.